2010
DOI: 10.1007/s11240-010-9835-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Escherichia coli heat-labile enterotoxin B subunit in transgenic watercress (Nasturtium officinale L.)

Abstract: A gene encoding the B subunit of the enterotoxigenic Escherichia coli heat-labile enterotoxin (LTB) was adapted to the optimized plant coding sequence, and fused to the endoplasmic reticulum retention signal SEKDEL in order to enhance its expression level and protein assembly in plants. The synthetic LTB (sLTB) gene was placed into a plant expression vector under the control of the CaMV 35S promoter, and subsequently introduced into the watercress (Nasturtium officinale L.) plant by the Agrobacterium-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Western blot analysis of these fruits detected a pentameric LTB protein with a molecular weight of about 45 kDa (Figure 5A). This result is similar to those obtained from different plant expression systems, such as those of tobacco (Kang et al 2003), lettuce (Kim et al 2007), Peperomia pellucida (Loc et al 2010a), and watercress (Loc et al 2011). However, there were only fruits of two transgenic plants expressing the LTB protein (#1 and #3).…”
Section: Detection Of Transgene In Transformed Plantssupporting
confidence: 88%
See 1 more Smart Citation
“…Western blot analysis of these fruits detected a pentameric LTB protein with a molecular weight of about 45 kDa (Figure 5A). This result is similar to those obtained from different plant expression systems, such as those of tobacco (Kang et al 2003), lettuce (Kim et al 2007), Peperomia pellucida (Loc et al 2010a), and watercress (Loc et al 2011). However, there were only fruits of two transgenic plants expressing the LTB protein (#1 and #3).…”
Section: Detection Of Transgene In Transformed Plantssupporting
confidence: 88%
“…Ten-day-old cotyledons were excised from in vitro-germinated seedlings and precultured on the shoot regeneration medium for 2 days. Then, we dropped the Agro-suspension onto the cotyledons (two drops onto each cotyledon) with a pipette (Loc et al 2011). After 2 days of cocultivation, cotyledons were cultured for 10 days on selection medium with 35 mg/l kanamycin (Km) and 200 mg/l cefotaxime (Cef ), for 10 days on selection medium with 50 mg/l Km and 200 mg/l Cef, and for 4 weeks on selection medium with 100 mg/l Km and 200 mg/l Cef.…”
Section: Methodsmentioning
confidence: 99%
“…Several plant models, such as tobacco, potato, maize, ginseng, carrot, and watercress have been utilized to assess the feasibility of developing a plant-based vaccine against ETEC (Haq et al 1995;Mason et al 1998;Chikwamba et al 2002;Kang et al 2006;Rosales-Mendoza et al 2007;Loc et al 2011). In general, these studies have confirmed that plantderived LTB retains both its antigenicity and immunogenicity compared with the native LTB.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, recombinant proteins produced in the whole plant or in plant cell cultures can be targeted to different subcellular compartments. The addition of the endoplasmic reticulum (ER) retention/retrieval sequence KDEL (Lys-Asp-Glu-Leu) to the C-terminal end of different recombinant proteins has been studied largely (Kim et al 2006(Kim et al , 2010aLoc et al 2010). It has been shown that KDEL increases recombinant protein accumulation levels in different plant expression systems, such as scFv antibodies in tobacco plants (Fiedler et al 1997) and rice callus tissues (Torres et al 1999), the 14D9 catalytic antibody in hairy roots of tobacco (Martínez et al 2005) and the spider silk protein in tobacco and potato plants (Scheller et al 2001).…”
Section: Introductionmentioning
confidence: 99%